PENGEMBANGAN MEDIA POP UP BOOK DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) MATA PELAJARAN IPAS MATERI SISTEM PENCERNAAN MANUSIA PADA SISWA KELAS V SDN TAMANSARI 1 - Nabila Althalya Putri; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto (STKIP Subang, 2026)
This study aims to develop a learning media in the form of a Pop-Up Book based on Contextual Teaching and Learning (CTL) for the human digestive system material for fifth-grade students at SDN Tamansari 1, as well as to determine the level of validity, practicality, and effectiveness of the media in improving students' understanding. This study was conducted because the use of learning media in the classroom is still limited in variety, causing students to have difficulty in understanding the human digestive system material. Therefore, a CTL-based Pop-Up Book media was developed, which is expected to help students understand the material more easily and attractively.This research uses the Research and Development (R&D) method with the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation.The research was conducted on fifth-grade students of SDN Tamansari 1, totaling 17 students. The research subjects involved material experts, media experts, teachers, and students. Data collection techniques were carried out through observation, interviews, questionnaires, as well as pretest and posttest. The instruments used consisted of validation sheets, teacher and student response questionnaires, and test questions to determine students' understanding of the human digestive system material.The research results show that the Contextual Teaching and Learning (CTL) -based Pop-Up Book media obtained a material expert validation percentage of 96.875% and a media expert validation of 95% with a very valid category. The practicality results of the media received a teacher response percentage of 96% and a student response of 95% with a very good category. The effectiveness results indicate an increase in student understanding with an average pretest score of 71.76 and an average posttest score of 92,35. The N-Gain calculation obtained a value of 0. 73 in the high category, while the percentage of student learning completeness reached 100% in the very effective category.Based on the results of the research, the Contextual Teaching and Learning (CTL) -based Pop-Up Book media was declared valid, practical, and effective for use in IPAS learning on the human digestive system material for fifth grade students at SDN Tamansari 1.